Self-Regulated Learning and Academic Stress of Islamic School Students: Mediating Effect of Student Engagement - Novarizka, Shalsabilla; Na'imah, Tri; Dwiyanti, Retno; Noveni, Nia Anggri; Satata, Dian Bagus Mitreka; Şen, Ayşenur (Universitas Muhammadiyah Yogyakarta, 2024)
Students in Islamic schools often experience academic stress due to the demands of studying general subjects and religious subjects. Self-regulated learning and student engagement are important to help students manage stress and optimize learning outcomes. The purpose of this study was to test the indirect effect of student engagement in mediating self-regulated learning on academic stress in students. This study used a saturated sample of 154 students who were analyzed quantitatively by testing the outer model and inner model with the SmartPLS application. The measuring instruments used were a modification of the Student-Life Stress Inventory (SLSI) scale (α = 0.989), a modification of the Student Engagement in School Questionnaire (SESQ) scale (α = 0.983), and a modification of the Assessing Academic Self-Regulated Learning scale (α = 0.988). The results of the inner model analysis showed that self-regulated learning had a significant effect on academic stress (β = 0.026; T = 2.239; P = 0.026), and student engagement entered as a mediator of the effect of self-regulated learning on academic stress remained significant (β = 0.023; T = 2.617; P = 0.009), which means it mediates partially. The R-Square results of self-regulated learning together with student engagement on academic stress showed a value of 0.994, which means that 99.4% of self-regulated learning and student engagement affect academic stress. The implication for Islamic schools is the importance of increasing self-regulated learning and student engagement to help students reduce academic stress by implementing student-centered learning strategies.